2022
DOI: 10.1002/slct.202200730
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 1‐Phenacylidene pyrrolo[3,2,1‐ij]quinolin‐2‐ones with Cyclic/Acyclic Enaminones and the Anticoagulant Activity of Synthesized Pyrrole‐Quinoline Derivatives

Abstract: A convenient strategy for the synthesis of pyrroles lineary linked to 4H‐pyrrolo[3,2,1‐ij]quinolin‐2(1H)‐ones is presented. The cyclization of (E)‐1‐(2‐oxo‐2‐phenylethylidene)‐4H‐pyrrolo[3,2,1‐ij]quinolin‐2‐ones with linear and cyclic enaminones proceeds both in the presence of p‐toluenesulfonic acid and triethylamine. The obtained compounds are characterised by atropoisomerism and keto‐enol tautomerism. The synthesized 1‐(2‐phenyl‐1H‐pyrrol‐3‐yl)‐4H‐pyrrolo[3,2,1‐ij]quinolin‐2(1H)‐ones were studied for antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In a number of our previous publications aimed at the synthesis and study of the anticoagulant activity of functional derivatives of pyrrolo[3,2,1- ij ]quinolin-2-ones, promising results were obtained and the promise of these structures in the synthesis of new inhibitors of factors Xa and XIa shown [ 55 , 56 , 57 , 58 , 59 , 60 ]. It has been shown that 5,6-dihydro-4 H -pyrrolo[3,2,1- ij ]quinolin-2-ones, and in particular 6-aryl-substituted ones, tend to exhibit higher activity compared to their unsaturated analogues [ 55 , 56 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of our previous publications aimed at the synthesis and study of the anticoagulant activity of functional derivatives of pyrrolo[3,2,1- ij ]quinolin-2-ones, promising results were obtained and the promise of these structures in the synthesis of new inhibitors of factors Xa and XIa shown [ 55 , 56 , 57 , 58 , 59 , 60 ]. It has been shown that 5,6-dihydro-4 H -pyrrolo[3,2,1- ij ]quinolin-2-ones, and in particular 6-aryl-substituted ones, tend to exhibit higher activity compared to their unsaturated analogues [ 55 , 56 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prompted by all the above-mentioned, and our previous studies [ 55 , 56 , 57 , 58 , 59 , 60 ], we designed and synthesized, based on the hybridization approach, new methyl 2-(4-oxo-2-(2-(2-oxo-5,6-dihydro-4 H -pyrrolo[3,2,1- ij ]quinolin-1(2 H )-ylidene)hydrazineyl)thiazol-5(4H)-ylidene)acetates and studied their inhibitory properties against blood clotting factors Xa and XIa in vitro.…”
Section: Introductionmentioning
confidence: 97%